Pregnant women's food consumption and associated socioeconomic factors in Brazil's primary health care - Geisyanne Soares da Silva; Natália Sales de Carvalho; Raquel Bezerra de Abreu; Beatriz Paiva Rocha; Isadora Ramos da Costa Rodrigues; Soraia Pinheiro Machado Arruda; Daniela Vasconcelos de Azevedo (Universidade de Fortaleza, 2020)
Objective: To assess food consumption by pregnant women receiving primary care and check for potential associations with socioeconomic variables. Methods: This cross-sectional study was conducted between April and November 2014 with a non-probability convenience sample of 201 pregnant women receiving primary care in Fortaleza, Ceará, Brazil. Food consumption data were collected using a Quantitative Food Frequency Questionnaire and socioeconomic data were collected using a specific instrument. Foods were quantified in portions and separated into the food groups described in the Dietary Guidelines for the Brazilian Population. STATA version 10.0 was used for statistical analysis. The normality of the quantitative variables was assessed by the Shapiro-Wilk test and the associations between food consumption and socioeconomic variables were assessed by the Mann-Whitney test with a 5% significance level. Results: There was a high consumption of calories (median of 3,991.6kcal) and all food groups, except legumes and vegetables. Lower levels of education were associated with higher consumption of cereals, tubers, roots and derivatives (p=0.004) and beans (p=0.041) and lower consumption of milk and dairy products (p=0.032). Women who lived with their partners exhibited higher consumption of sugars and sweets (p=0.048). Conclusion: The pregnant women's food consumption significantly exceeded the recommended number of calories and portions of the food groups - except for the legumes and vegetables group. Socioeconomic variables were associated with the consumption of certain food groups.